2000
DOI: 10.1046/j.1365-313x.2000.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective splicing of the first nad4 intron is associated with lack of several complex I subunits in the Nicotiana sylvestris NMS1 nuclear mutant

Abstract: SummaryIn this work, we provide evidence for the existence of a nuclear factor involved in the splicing of a speci®c mitochondrial intron in higher plants. In the Nicotiana sylvestris nuclear NMS1 mutant, defective in both vegetative and reproductive development, the ®rst intron of the nad4 transcript encoding the complex I NAD4 subunit is not removed, whatever the tissue analysed. Transcript patterns of other standard mitochondrial genes are not affected in NMS1. However, numerous polypeptides are missing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 59 publications
3
57
0
Order By: Relevance
“…The nuclear gene affected in this mutant has a high similarity to group II intron maturases, and the affected plants show impaired splicing of the mitochondrial nad4 transcript. The molecular phenotype of this mutant resembles that of the NMS1 mutant from N. sylvestris, also specifically defective in splicing of nad4 transcripts (Brangeon et al, 2000). Complex I activity was not measured in the css1 mutant, but like the other previously described Arabidopsis Complex I mutants, the overall phenotype appears to be milder than the otp43 mutant described here.…”
Section: Plant Complex I Mutantsmentioning
confidence: 43%
See 1 more Smart Citation
“…The nuclear gene affected in this mutant has a high similarity to group II intron maturases, and the affected plants show impaired splicing of the mitochondrial nad4 transcript. The molecular phenotype of this mutant resembles that of the NMS1 mutant from N. sylvestris, also specifically defective in splicing of nad4 transcripts (Brangeon et al, 2000). Complex I activity was not measured in the css1 mutant, but like the other previously described Arabidopsis Complex I mutants, the overall phenotype appears to be milder than the otp43 mutant described here.…”
Section: Plant Complex I Mutantsmentioning
confidence: 43%
“…A nuclear mutant almost lacking Complex I was observed in N. sylvestris (Brangeon et al, 2000), while three nuclear mutants affected in Complex I have been identified in Arabidopsis (Lee et al, 2002;Perales et al, 2005;Nakagawa and Sakurai, 2006). Each of these mutants is defective in a different gene, and the phenotypes of these mutants are quite varied.…”
Section: Introductionmentioning
confidence: 99%
“…Complex I dysfunctions have been previously associated with plants having growth to flowering developmental defects (Gutierres et al 1997;Brangeon et al 2000;Sabar et al 2000;Pineau et al 2005;Garmier et al 2008). Accordingly, nMat2 plants demonstrated slow growth, late flowering, and were partially sterile ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…A nuclear mutation in Nicotiana sylvestris (nms1) was shown to disrupt the splicing of the first intron in the nad4 transcript (Brangeon et al 2000), however the identity of this gene remains unknown. Recently, a pentatricopeptide repeat protein (OPT43) was found to function specifically in the trans-splicing activity of nad1 intron1 in Arabidopsis mitochondria (de Longevialle et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the nad genes involves a combination of cis-and trans-splicing events that remove group II introns from the transcripts (Bonen, 2008). Several RNA-binding proteins are known to be involved in mitochondrial splicing events in nad transcripts: ORGANELLE TRANSCRIPT PROCESS-ING43 (OTP43; trans-splicing of nad1 intron 1; Falcon de Longevialle et al, 2007), ABSCISIC ACID OVERLY SENSITIVE5 (cis-splicing of nad2 intron 3; Liu et al, 2010), RCC1/UV-B RESISTANCE8/GUANINE NUCLEOTIDE EXCHANGE FACTOR3 (RUG3; (trans-splicing of nad2 intron 2 and cis-splicing of intron 3; Kühn et al, 2011), NUCLEAR MALE STERILE1 (cis-splicing of nad4 intron 1; Brangeon et al, 2000), BUTHIONINE SULFOMIXINE-INSENSITIVE ROOTS6 (BIR6; cis-splicing of nad7 intron 1; Koprivova et al, 2010), and other less-specific factors such as PUTATIVE MITOCHONDRIAL RNA HELI-CASE2 (PMH2; Köhler et al, 2010), maturases (nMAT1, nMAT2, and nMAT4; Keren et al, 2009Keren et al, , 2012Brown et al, 2014;Cohen et al, 2014), and the MITOCHONDRIAL CHLOROPLAST RNA SPLICING ASSOCIATED FACTORlike SPLICING FACTOR1 (mCSF1; Zmudjak et al, 2013) affecting numerous introns.…”
mentioning
confidence: 99%